Necessity of Da’wa Communication for Reformation in Muslim Guardianship Laws in India - Pazhayakath, Najla; Kesari A, Vani (Universitas Islam Negeri Mataram, 2024)
The diversity of religions, cultures, and languages is an inherent feature of Indian democracy. These kinds of legal pluralism arrangements are found in the area of personal laws in India. Since 1985, India has witnessed a direct conflict between Muslim personal law and secular laws. Recently, one of the High Courts in India reaffirmed that the mother of the child has no right to be considered as the natural guardian of her child. The gender disparities with the guardianship laws under Islamic law are being exposed again by this decision. Inadequate understanding and interpretation of religious texts usually lead to these kinds of disparities. Da’wa can help refresh and reform Sharia by encouraging Muslims to think closely about how it is used and understood and to seek better solutions to today's problems. The guardianship laws in India now need to be changed in light of modern da’wa communication. This article explains the importance of da'wa communication and how it should be applied to reinterpret Muslim personal laws in India. This article concludes with a comment that modern da’wa communication is necessary to interpret guardianship laws under sharia from a liberal dynamic and forward-looking perspective without rejecting the value of Islamic jurisprudence and the All India Muslim Personal Law Board should take measures to achieve gender parity in Muslim guardianship laws through efficient da'wa communication.